Comparative transcriptomic and metabolomic analysis revealed molecular mechanism of two wheat near-isogenic lines response to nitrogen application - Zhang, X.; Ding, Y.; Ma, Q.; Li, F.; Tao, R.; Li, T.; Zhu, X.
Nitrogen (N)is an essential nutrient element required for plant growth, and the development of wheat varieties with high nitrogen use efficiency (NUE)is an urgent need for sustainable crop production. However, the molecular mechanism of NUE between diverse wheat varieties in response to N application remains unclear. To reveal the possible molecular mechanisms underlying this complex phenomenon, we investigated the transcriptional and metabolic changes of flag leaves of two wheat near-isogenic lines (NILs)differing in NUE under two N fertilizer treatments. Comparative transcriptome analysis indicated that the expression levels of the genes responsible for carbon and nitrogen metabolism were significantly higher in high-NUE wheat. The metabolome comparison revealed that the activity of the tricarboxylic acid (TCA)cycle was enhanced in high-NUE wheat, while reduced in low-NUE wheat after the N fertilizer application. Additionally, amino acid metabolism increased in both wheat NILs but more increased in high-NUE wheat. In summary, more upregulated transcripts and metabolites were identified in high-NUE wheat, and this study provides valuable new insights for improving NUE in wheat.
Keywords: CARBON METABOLISM; METABOLOME; NITROGEN; NITROGEN METABOLISM; TRANSCRIPTOME; WHEAT